The Role of Brand Trust in Mediating Brand Image Towards Loyalty of Visitors in Lake Toba - Emma Novirsari; Sungguh Ponten Pranata (Syntax Corporation Indonesia, 2021)
Lake Toba is the target of a world-class tourist destination planned by the Indonesian government. Various policies and strategies were made to achieve these targets. The focus of the study in this study emphasizes the role of brand trust in mediating brand image on visitor loyalty in Lake Toba. The target population and sample in this study were 125 visitors to Lake Toba selected by accidental sampling. The path analysis in this study was chosen to see the direct and indirect role of brand trust in mediating brand image towards loyalty. The results showed that 1) brand image directly had a positive and significant effect on the brand trust of visitors to Lake Toba. 2) brand image directly has a positive and significant effect on visitor loyalty at Lake Toba. 3) indirectly, brand trust has a role in mediating brand image towards visitor loyalty at Lake Toba.